Peran Pengembangan Karir Dan Disiplin terhadap Pencapaian Kinerja Pegawai pada Kejaksaan Negeri Kabupaten Bogor - Dewi Yanti; Nurlaela Eva Puji Lestari (MOTIVASI, 2025)
Purpose– The research background stems from the observed decline in employee performance, attributed to obstacles in career development and low work discipline levels. The main goal is to determine both the partial and simultaneous effects of career development and discipline on employee performance at the Bogor District Attorney's Office. Design/methodology– The research employs a quantitative approach, gathering data through questionnaires distributed to 80 employees. The collected data were analyzed using validity and reliability tests, classical assumption tests, and multiple linear regression analysis with SPSS version 23 software. Findings - Results reveal that career development positively and significantly affects employee performance, with a regression coefficient of 0.262. Work discipline exerts a stronger influence, with a regression coefficient of 0.423. Together, these variables explain 62.8% of the variance in employee performance (Adjusted R Square: 0.628). Practically, these findings provide a solid foundation for management at the Bogor District Attorney’s Office to focus on strengthening career development programs and work discipline as key strategies to improve performance. Theoretically, this study reinforces the crucial role of career development and work discipline as key variables in human resource management within government institutions.